Nature and Realism in Schelling's Philosophy - Emilio Carlo Corriero
In recent years the international philosophical debate around the so-called 'new' realism has undoubtedly aroused renewed interest in the philosophical positions of Schelling, an author who right in the midst of the philosophical project of German Idealism, forcefully insinuated the natural-realistic objection, leading to a breakaway towards contemporary thinking. In this book Iain Hamilton Grant, Alistair Welchman, Emilio Carlo Corriero, Manfred Frank, Andrea Dezi, Olaf Müller, Maurizio Ferraris display their perspectives on the topic.